New & selected poems - Justice, Donald Rodney 1925-2004 (Knopf, 1995)
The present volume brings to mind again one of the most interesting aspects of Justice's poetry: his dedication to formal craftsmanship and his use of it in dealing with contemporary matters; so that a recondite poetic form (the pantoum) is made to hold a commentary on the 1930s in the poem called "Pantoum of the Great Depression."
Keywords: Poems